Underestimates of unintentional firearm fatalities: comparing Supplementary Homicide Report data with the National Vital Statistics System. Issue 3 (1st September 2002) - Barber, C; Hemenway, D; Hochstadt, J; Azrael, D
Abstract : Objective: A growing body of evidence suggests that the nation's vital statistics system undercounts unintentional firearm deaths that are not self inflicted. This issue was examined by comparing how unintentional firearm injuries identified in police Supplementary Homicide Report (SHR) data were coded in the National Vital Statistics System. Methods: National Vital Statistics System data are based on death certificates and divide firearm fatalities into six subcategories: homicide, suicide, accident, legal intervention, war operations, and undetermined. SHRs are completed by local police departments as part of the FBI's Uniform Crime Reports program. The SHR divides homicides into two categories: "murder and non-negligent manslaughter" (type A) and "negligent manslaughter" (type B). Type B shooting deaths are those that are inflicted by another person and that a police investigation determined were inflicted unintentionally, as in a child killing a playmate after mistaking a gun for a toy. In 1997, the SHR classified 168 shooting victims this way. Using probabilistic matching, 140 of these victims were linked to their death certificate records. Results: Among the 140 linked cases, 75% were recorded on the death certificate as homicides and only 23% as accidents. Conclusion: Official data from the National Vital Statistics System almost certainly undercount firearm accidents when the victim is shot by another person.